2021
DOI: 10.1093/humrep/deab063
|View full text |Cite
|
Sign up to set email alerts
|

Association between follicular fluid phthalate concentrations and extracellular vesicle microRNAs expression

Abstract: STUDY QUESTION Are phthalate metabolite concentrations in follicular fluid (FF) associated with the expression of extracellular vesicle microRNAs (EV-miRNAs)? SUMMARY ANSWER Phthalate metabolite concentrations are associated with the expression of EV-miRNA and their associated pathways in FFs. WHAT IS KNOWN ALREADY Phthalate metabolites were recently detected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 33 publications
0
15
1
Order By: Relevance
“…Although phthalates have short half-lives (33,34), this study has demonstrated the accumulation of all six phthalate metabolites in the FF of 176 women with a detection rate of 98.9%-100% (Table 1), affirming their presence in the ovarian microenvironment (35)(36)(37)(38). Follicular fluid comprises a delicate balance of hormones, growth factors, reactive oxygen species, and antioxidants working in tandem toward the developmental potential of the oocyte (39).…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Although phthalates have short half-lives (33,34), this study has demonstrated the accumulation of all six phthalate metabolites in the FF of 176 women with a detection rate of 98.9%-100% (Table 1), affirming their presence in the ovarian microenvironment (35)(36)(37)(38). Follicular fluid comprises a delicate balance of hormones, growth factors, reactive oxygen species, and antioxidants working in tandem toward the developmental potential of the oocyte (39).…”
Section: Discussionmentioning
confidence: 59%
“…The same research group in an earlier study by Du Y et al (35), showed that even at low concentrations, certain phthalate metabolites, including MEP, MBP, and metabolites of DEHP in the FF of (n ¼ 194) women could alter the levels of intrafollicular reproductive hormones, suggesting the adverse effect of phthalate exposure on theca and granulosa cell function. In a more recent study, Barnett-Itzhaki Z et al (38) showed a significant correlation between relatively low levels of phthalate metabolites such as MEP and metabolites of DiNP and DiDP detected in the FF of (n¼105) women and follicular extracellular vesicle microRNAs profiles, suggesting impairment of pathways involved in the oocyte development, maturation, and fertilization. It is therefore imperative that women who are trying to conceive should reduce their exposure to phthalates by modifying their lifestyle and consumption patterns.…”
Section: Discussionmentioning
confidence: 98%
“…Phthalate metabolites altered the follicular miRNA profile (miR-375 was downregulated), thereby impairing the pathways involved in oocyte development, maturation, and fertilization, as well as interfering with female fertility and embryo mass. 30,31 Furthermore, phthalate exposure decreased miRNA-mRNA linkage and identified miR-375 as a potential critical regulator of breast carcinogenesis. 37 Here, we found that miR-375 was significantly downregulated in zebrafish upon DEHP exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies indicated that the expression of miR-375 was altered by DEHP. , miRNA-mRNA prediction indicated that pre-mRNA processing factor 3 ( PRPF3 ) is a likely target mRNA for miR-375 whose expression is altered by DEHP exposure. However, the interrelation between miR-375 and PRPF3 has not yet been confirmed experimentally.…”
Section: Introductionmentioning
confidence: 99%
“…We explored CDK2 related miRNAs from Targetscan 16 ( Barnett-Itzhaki et al, 2021 ), miRWalk 17 ( Sheng L. P. et al, 2021 ), mirDB 18 ( Ren et al, 2021 ), Starbase 19 ( Li et al, 2014 ). All miRNAs from four databases were analyzed by Venn map 20 .…”
Section: Methodsmentioning
confidence: 99%